Traumatic Spigelian hernia in a child - Fatma Thamri; Senda Houidi; Arije Zouaoui; Bochra Aziza; Yasmine Houas; Yosra Kerkeni; Sondes Sahli; Riadh Jouini (Elsevier, 2021)
Spigelian hernia is an uncommon surgical condition in children and accounts for only 1% of all abdominal hernias. Its traumatic origin has been described sporadically in the literature.We report a case of a 9-year-old boy, brought to the emergency department 2 hours after abdominal trauma caused by a bicycle's handlebar grip at the lower abdomen, complaining of abdominal pain. Apart from edema, bruising and tenderness of the right of lower abdomen, physical examination showed a 1.5 * 2 cm reducible swelling lateral to the rectus muscle and a 1-cm facial defect of the anterior abdominal wall at the same site. Ultrasonography concluded to diastasis between the rectus abdominis muscle and the broad abdominal muscles with evidence of a hernia sac. The diagnosis of traumatic Spigelian hernia was retained and the patient was operated on. He had primary repair of the defect in layers using interrupted sutures. He was discharged in the same day and the aftermath of surgery was uneventful.In conclusion, traumatic Spigelian hernias are rare entities in children which diagnosis should be considered following blunt abdominal trauma. We recommend careful abdominal examination after trauma to highlight swelling and/or aponeurotic defect.